Fiber bragg grating dilatometry in extreme magnetic field and cryogenic conditions - Jaime, Marcelo (2017)
In this work, we review single mode SiO2 fiber Bragg grating techniques for dilatometry studies of small single-crystalline samples in the extreme environments of very high, continuous, and pulsed magnetic fields of up to 150 T and at cryogenic temperatures down to <1 K. Distinct millimeter-long materials are measured as part of the technique development, including metallic, insulating, and radioactive compounds. Experimental strategies are discussed for the observation and analysis of the related thermal expansion and magnetostriction of materials, which can achieve a strain sensitivity (DL/L) as low as a few parts in one hundred million (≈10-8). The impact of experimental artifacts, such as those originating in the temperature dependence of the fiber’s index of diffraction, light polarization rotation in magnetic fields, and reduced strain transfer from millimeter-long specimens, is analyzed quantitatively using analytic models available in the literature. We compare the experimental results with model predictions in the small-sample limit, and discuss the uncovered discrepancies.